Digital Transformation and Generation Z’s Interest in Islamic Banking Products: Evidence from Lampung Province - Salsa Nabila; Muhammad Iqbal Fasa (DPPM Universitas Pelita Bangsa, 2025)
Digital transformation has become a global phenomenon that affects various sectors, including Islamic banking business. The purpose of this study is to analyze the impact of digital transformation on the benefits of generation Z when using Islamic banking products in Lampung province. Known as the generation of technology literature, Generation Z is interested in efficient and easily accessible banking services, and is easily accessible to the values they recognize. The research method used is literature research and secondary data analysis, identifying trends in digital transformation in Islamic banking and generation z preferences for digital-based financial services. The results of the study indicate that digital transformation such as the development of mobile banking applications, digital payment services, and financial platforms based on Sharia will increase the interest of generation Z in Islamic banking products. Factors such as easy access, transaction speed, and compliance with Sharia principles are the main drivers. This study includes recommendations on Islamic banking operations to ensure that Islamic banking operations continue to develop digital innovations to attract Power Z and that the services provided remain in accordance with Sharia principles. This study is expected to be a reference for the development of Islamic banking strategies, especially in the digital era, in Lampung province. In addition, this research contributes to the existing literature by providing insights into the intersection of digital transformation and generational behavior in Islamic banking, and offers policy implications for Islamic banking institutions to design targeted digital strategies that align with the expectations and preferences of Generation Z.